A systematic review of the efficacy, effectiveness and cost-effectiveness of workplace-based interventions for the prevention and treatment of problematic substance use - Morse, Ashleigh K.; Askovic, Mina; Sercombe, Jayden; Dean, Kate; Fisher, Alana; Marel, Christina; Chatterton, Mary-Lou; Kay-Lambkin, Frances; Barrett, Emma; Sunderland, Matthew; Harvey, Logan; Peach, Natalie; et al. (Frontiers in Public Health, 2022)
Employee alcohol and other drug use can negatively impact the workplace, resulting in absenteeism, reduced productivity, high turnover, and worksite safety issues. As the workplace can influence employee substance use through environmental and cultural factors, it also presents a key opportunity to deliver interventions, particularly to employees who may not otherwise seek help. This is a systematic review of workplace-based interventions for the prevention and treatment of problematic substance use. Five databases were searched for efficacy, effectiveness and/or cost-effectiveness studies and reviews published since 2010 that measured use of psychoactive substances (i.e., alcohol, cannabis, hallucinogens, inhalants, opioids, sedatives, hypnotics, anxiolytics, and stimulants) as a primary or secondary outcome, in employees aged over 18. Thirty-nine articles were identified, 28 describing primary research and 11 reviews, most of which focused solely on alcohol use. Heterogeneity between studies with respect to intervention and evaluation design limited the degree to which findings could be synthesized, however, there is some promising evidence for workplace-based universal health promotion interventions, targeted brief interventions, and universal substance use screening. The few studies that examined implementation in the workplace revealed specific barriers including lack of engagement with e-health interventions, heavy use and reluctance to seek help amongst male employees, and confidentiality concerns. Tailoring interventions to each workplace, and ease of implementation and employee engagement emerged as facilitators. Further high-quality research is needed to examine the effectiveness of workplace substance use testing, Employee Assistance Programs, and strategies targeting the use of substances other than alcohol in the workplace. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=227598, PROSPERO [CRD42021227598].